Small Molecules with Similar Structures Exhibit Agonist, Neutral Antagonist or Inverse Agonist Activity toward Angiotensin II Type 1 Receptor - Miura, Shin-ichiro (Public Library of Science, 2012)
Small differences in the chemical structures of ligands can be responsible for agonism, neutral antagonism or inverse agonism toward a G-protein-coupled receptor (GPCR). Although each ligand may stabilize the receptor conformation in a different way, little is known about the precise conformational differences. We synthesized the angiotensin II type 1 receptor blocker (ARB) olmesartan, R239470 and R794847, which induced inverse agonism, antagonism and agonism, respectively, and then investigated the ligand-specific changes in the receptor conformation with respect to stabilization around transmembrane (TM)3. The results of substituted cysteine accessibility mapping studies support the novel concept that ligand-induced changes in the conformation of TM3 play a role in stabilizing GPCR. Although the agonist-, neutral antagonist and inverse agonist-binding sites in the AT(1) receptor are similar, each ligand induced specific conformational changes in TM3. In addition, all of the experimental data were obtained with functional receptors in a native membrane environment (in situ).